Academic Administration in the 21st Century of Primary Schools in Chaiya District, Surat Thani Province under the Office of Surat Thani Primary Educational Service Area 2 - Suwannatamma, Porntip; Somsathan, Prapatsorn (Journal of Graduate MCU KhonKaen Campus, 2025)
This research aimed to study academic administration in the 21st century, study 21st century learning skills that affect student achievement, and study the relationship between academic administration in the 21st century and 21st century learning skills that affect student achievement of primary schools in Chaiya District, Surat Thani Province, under Surat Thani Primary Educational Service Area Office 2. The sample group used in the research was 159 teachers. The research instrument was a 5-level rating scale questionnaire with content validity of 1.00 and reliability of 0.95. The statistics used for data analysis were percentage, mean, standard deviation, and Pearson’s product moment correlation coefficient. The results of the research were as follows: 1. Academic administration in the 21st century of primary schools in Chaiya District, Surat Thani Province, under the Office of the Surat Thani Primary Educational Service Area 2, found that overall it was at the highest level. The aspect with the highest average value was measurement and evaluation, while the aspect with the lowest average value was research to develop the quality of education in educational institutions. 2. The 21st century learning skills that affect the achievement of students in primary schools in Chaiya District, Surat Thani Province, under the Office of Surat Thani Primary Educational Service Area 2, found that overall, the level of impact on the achievement of students was at a high level. The areas with the highest average values were cooperation skills, teamwork, and leadership. The areas with the lowest average values were critical thinking skills and problem-solving skills. 3. The relationship between academic administration in the 21st century and learning skills in the 21st century that affect the achievement of students in primary schools in Chaiya District, Surat Thani Province, under the Office of the Surat Thani Primary Educational Service Area 2, found that there was a high level of positive relationship with statistical significance at the 0.01 level.